Population-level Metagenomics Uncovers Distinct Effects of Multiple Medications on the Human Gut Microbiome - Nagata, Naoyoshi; Nishijima, Suguru; Miyoshi-Akiyama, Tohru; Kojima, Yasushi; Kimura, Moto; Aoki, Ryo; Ohsugi, Mitsuru; Ueki, Kohjiro; Miki, Kuniko; Iwata, Eri; Hayakawa, Kayoko; Ohmagari, Norio; et al. (Gastroenterology (New York, N.Y. 1943), 2022)
Medication is a major determinant of human gut microbiome structure, and its overuse increases the risks of morbidity and mortality. However, effects of certain commonly prescribed drugs and multiple medications on the gut microbiome are still underinvestigated. We performed shotgun metagenomic analysis of fecal samples from 4198 individuals in the Japanese 4D (Disease, Drug, Diet, Daily life) microbiome project. A total of 759 drugs were profiled, and other metadata, such as anthropometrics, lifestyles, diets, physical activities, and diseases, were prospectively collected. Second fecal samples were collected from 243 individuals to assess the effects of drug initiation and discontinuation on the microbiome. We found that numerous drugs across different treatment categories influence the microbiome; more than 70% of the drugs we profiled had not been examined before. Individuals exposed to multiple drugs, polypharmacy, showed distinct gut microbiome structures harboring significantly more abundant upper gastrointestinal species and several nosocomial pathobionts due to additive drug effects. Polypharmacy was also associated with microbial functions, including the reduction of short-chain fatty acid metabolism and increased bacterial stress responses. Even nonantibiotic drugs were significantly correlated with an increased antimicrobial resistance potential through polypharmacy. Notably, a 2-time points dataset revealed the alteration and recovery of the microbiome in response to drug initiation and cessation, corroborating the observed drug-microbe associations in the cross-sectional cohort. Our large-scale metagenomics unravels extensive and disruptive impacts of individual and multiple drug exposures on the human gut microbiome, providing a drug-microbe catalog as a basis for a deeper understanding of the role of the microbiome in drug efficacy and toxicity. [Display omitted] This population-level metagenomic analysis reveals extensive effects of various drugs and multiple medications on the gut microbiome.